2009
DOI: 10.1161/circulationaha.108.837278
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Comprehensive Assessment of Cardiac Troponin T Testing After Coronary Artery Bypass Graft Surgery

Abstract: Background-The significance and clinical role of cardiac troponin testing after coronary artery bypass grafting remain unclear. Methods and Results-Cardiac troponin T (cTnT) was measured during the first 24 hours after coronary artery bypass graft surgery in 847 consecutive patients. Only 17 patients (2.0%) had new Q waves or left bundle-branch block after surgery; however, cTnT elevation was observed in nearly all subjects, with a median cTnT concentration of 1.08 ng/mL overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 28 publications
6
62
2
2
Order By: Relevance
“…3,7 A potential reason for our finding of a lower area under the ROC curve may be that the superior sensitivity of the hs-TnT assay may have compromised its specificity and positive predictive value…”
Section: Dual Elevation Of High-sensitivity Troponin Plus Ecg And/or mentioning
confidence: 96%
See 1 more Smart Citation
“…3,7 A potential reason for our finding of a lower area under the ROC curve may be that the superior sensitivity of the hs-TnT assay may have compromised its specificity and positive predictive value…”
Section: Dual Elevation Of High-sensitivity Troponin Plus Ecg And/or mentioning
confidence: 96%
“…2,3 Several studies have found that isolated troponin rise after CABG, measured with contemporary assays, independently predicts adverse outcomes. [3][4][5][6][7] High-sensitivity troponin assays have recently been developed, 8 being more sensitive than contemporary assays at detecting lower troponin levels. 1,9 The properties and utility of these assay may be different after CABG, and…”
Section: Introductionmentioning
confidence: 99%
“…Surgery in these patients is associated with an elevated overall operative risk of 5-6% compared to 1% in lower-risk patients [2], as well as an increased risk of periprocedural myocardial injury (as measured by serum CK-MB, Troponin T or I) [3], acute kidney injury (AKI) [4] and stroke [5], the presence of which are associated with worse clinical outcomes [6][7][8][9][10][11][12][13][14][15][16]. Myocardial injury during CABG surgery may be attributed to different mechanisms, including most importantly acute myocardial ischemiareperfusion injury (IRI), but also inflammatory response to the extraneous substances in the cardiopulmonary bypass circuit, left ventricular over-distension, coronary atheroembolism [17], increased cardiac workload during the intraoperative period, and direct myocardial injury due to retraction and handling of the heart [18].…”
mentioning
confidence: 99%
“…Inicialmente, a reprodutibilidade dos estudos é baixa em razão do reduzido número de indivíduos com seguimento a longo prazo e a utilização de desfechos compostos de menor relevância, como a necessidade de suporte ventilatório mecânico (83,87) . Não houve correlação evidente entre biomarcadores cardíacos com infarto do miocárdio documentado por autópsia, novo realce tardio em RMC com gadolínio ou aparecimento de nova onda Q ou BRE novo (88)(89)(90) .…”
Section: Dosagem De Biomarcadoresunclassified
“…O fato provoca ampla variação nos valores de pico médios de troponinas e que, frequentemente, estão acima de 10 vezes o percentil 99 (83) . Essa variabilidade prejudica a interpretação dos resultados e aumenta erroneamente o número de pacientes com diagnóstico de infarto tipo 5.…”
Section: Dosagem De Biomarcadoresunclassified